Pelatihan Pembuatan Deterjen Cair Melalui Digital E-Commerce Shopee untuk Mendukung Peningkatan Ekonomi UMKM Masyarakat Desa Paya Perupuk oleh KKN 146 UINSU - Muniruddin Muniruddin; Uswatun Hasanah Lubis; Hafizah Ismayati; Muhammad Arif (Journal Of Business, Finance, and Economics (JBFE), 2024)
Training on making liquid detergent is one of the economic empowerment efforts for the community in Paya Perupuk Village, which is carried out by the Real Work Lecture Group (KKN) 146 of the North Sumatra State Islamic University (UINSU). This training aims to improve people's skills in producing household products, especially liquid detergent, as well as utilizing e-commerce platforms, such as Shopee, for product marketing. This activity is to encourage economic growth of Micro, Small and Medium Enterprises (MSMEs) as part of the home industry in the village. This article discusses the training process, the results achieved, and the impact on the local economy.